Food consumption pattern for hypertension patient in Klaten Regency, Central Java Province, Indonesia - Nasyaroeka, Ayu Eka Buana Dewi; Solikhah, Solikhah; Lianawati, Lianawati (Jurnal Cakrawala Promkes, 2024)
Hypertension, commonly known as high blood pressure, is a grave medical condition that serves as a catalyst for the onset of various other ailments, each bearing significant consequences that may ultimately lead to fatality. Unhealthy eating habits, such as consuming foods heavy in sugar, sodium, or saturated fat, are the primary cause of elevated incidences of hypertension. This research aimed to determine the relationship between food consumption patterns in hypertensive patients. This study used a cross-sectional study design conducted on outpatients at the Prambanan Health Center, Prambanan District, Klaten Regency, from December 2022 to February 2023.  The population used in this study were all patients with hypertension in Klaten Regency, which amounted to 2,884 people from January until December 2021. The research sample was taken randomly with a value a of 5%. Based on the sample calculation, the sample size was 339 hypertension sufferers. Data analysis used in this study was univariate and bivariate analysis using the chi-square test with a degree of confidence of 95%. The results of this study indicate that the level of salt, fiber, and fat consumption is not related to sufferer hypertension. Maintaining a nutritious diet and engaging in physical activity as part of a healthy lifestyle may also help lower blood pressure. This study supports the hypothesis that dietary variety might be important for the future. Future research endeavors ought to delve into the intricate relationship between dietary practices and blood pressure across diverse cultural contexts, elucidating how variations in dietary habits influence blood pressure levels. Furthermore, it is imperative to investigate the potential repercussions of elevated blood pressure on various cultural groups, shedding light on tits unique impacts ondifferent societal frameworks.